Skin care in women after 45 years of age (Journal of Face Aesthetics, 2022)
Introduction. Proper skin care, including cleansing, hydration, protection against sun, has meaningful impact on one’s look and function. Skin care should always be adjusted to its needs that changes through years of life.Aim. The aim of the study was to assess the knowledge about skincare at women past 45.Material and Methods. Fifty‑six women participated in this study. The research instrument was a questionnaire, which contained twenty‑seven questions. The questionnaire was put online. Inclusion criteria: age after 45 and female gender.Results. Women past 45 didn't care correctly about their own skin. Their knowledge was not proper considering photoprotection and regular application of cosmetics with UV filters. Women past 45 didn’t have enough knowledge about photoprotection and they didn’t use it adequately. Women with less amount of skin lesions, which was related with skin aging, were more pleased about their appearance than women, who have more skin changes.Conclusions. Women after the age of 45 applied most of all moisturizers and anti‑wrinkle creams in their skincare routine. Women after the age of 45 require more education about how to use photoprotection in the right and effective way. The less skin changes, connected with skin aging, the better frame of mind about skin appearance at women past 45.
Keywords: skin diagnostics; cutometer; coefficient of elasticity – parameter R8/R0